Analisis Spasial Keterjangkauan Jarak Layanan dan Pola Persebaran Lembaga Pendidikan Menggunakan Buffering dan Nearest Neighbor Analysis - Widya Ayu Lestari; Wahju Tjahjo Saputro; Hanifatus Sa’diyah Widihasaniputri (Bulletin of Computer Science Research, 2026)
Equitable access to religious educational services is strongly influenced by the spatial distribution and service coverage of educational institutions. However, the growth of educational facilities is not always accompanied by balanced spatial planning, which can lead to accessibility disparities. This study aims to analyze service accessibility and spatial distribution patterns of educational institutions in Tlogomulyo District, Temanggung Regency, using a Geographic Information System (GIS) based quantitative descriptive analysis approach. Service accessibility was assessed using buffer analysis with a 500-meter radius, referring to neighborhood-scale educational facility service standards outlined in SNI 03-1733-2004, representing a reasonable service distance within rural settlement contexts, while spatial distribution patterns were examined using Nearest Neighbor Analysis (NNA) implemented in QGIS. The results indicate that most residential areas are within the service coverage of educational institutions, although several locations remain underserved. The NNA index value of 0.93 with a z-score of ?0.79 at a significance level of ? = 0.05 suggests a weak clustered distribution pattern that is not statistically significant at the 95% confidence level. These findings indicate that the spatial distribution of educational institutions tends to follow settlement patterns but has not yet achieved spatial equity. This study highlights the importance of GIS-based spatial analysis as a decision-support tool for planning and optimizing the distribution of religious educational services to promote equitable access within the study area.